Дослідження робочих характеристик трьохфазного асинхронного електропривода з тиристорним регулятором напруги - Голодний, І. М.; Синявський, О. Ю.; Санченко, О.В. (Енергетика і автоматика, 2017)
UDK 621.3.067 RESEARCH OF WORKING CHARACTERISTICS OF THREE-PHASE ASYNCHRONOUS ELECTRIC DRIVE WITH THYRISTOR VOLTAGE REGULATOR I. Golodny, А. Sinyavsky, A. Sanchenko Introduction. For the regulated electric induction often used semiconductor voltage converters, in particular thyristor regulators, which in the technical literature little attention is paid to research performance. This is due to the complexity or high cost of such research. With the development of computer simulation appeared opportunity to deepen the study of various electric performance and compare the results with actual data real electric ventilation installation with the station management "Klimatyka 1". Analysis of recent researches and publications. For low-power asynchronous motors with short-closed rotor relatively easy to adjust the speed of change in voltage on the stator, as they are soft on mechanical characteristics of working. The most simple and cheap for the specified regulation is amplitude voltage regulators with fan electric load. The aim of the work is to reduce the time and costs for studying a controlled asynchronous electric drive by computer simulation and to confirm the adequacy of the results obtained on the model and physical installation. The materials and methods of research. The analysis of the performance of the regulated electric drive with the chosen control method was carried out using the provisions of the electric drive theory and statistical methods for processing the results of research on the physical and computer model in the MatLab system. The results of the research. To analyze the characteristics of the model of three-phase asynchronous electric consisting of induction motor AIRP80-A6U2. The engine has an increased resistance of the winding rotor, which causes increased slip at nominal moment, high starting torque and low starting current multiplicity. This engine is currently under load fan speed control allows for a wide range of voltage fed. Block Gain, Product 1, Product 2 and Constant created 2 fan load to the motor (the time changes are not taken into account). Versatile measurement units Machines Messurement Demux, Display and Scope obtain quantitative values and observe the instantaneous speed and electromagnetic torque of the engine and block XY Graph vizializuye mechanical characteristics of the engine. Three-phase thyristor voltage regulator consists of three single-phase regulators, each with its own control system. Thyristor opening angle for all phases is set Constant block 1. Research conducted performance by changing the voltage of 0,34UN to UN. For adjusting the characteristics w* = f(U*) velocity recorded at the appropriate voltage measuring unit of the Display (upper value). The value of power for power characteristics P* = f(U*) defined as a product P* = Mw/PN, where M - the current value of the electromagnetic torque of the electric motor (Block Display lower value). The performance obtained in computer models resulted in relative terms, ie the current values of the corresponding split of the nominal value. To check the reliability of the results on the computer model studies were conducted on a laboratory bench regulated electric axial fan VO-7,1M engine AIRP80A6U2. Line voltage on the electric motor changed by using voltage thyristor converter station "Klimatyka-1" phase-controlled pulse ranges from 120 to 380 V. In this set of measuring K-505 measured voltage and power, and tachometer D-1MM – rotor speed engine. The research received dependence in relative units w*=f(U*), P*=f(U*). When comparing the results obtained, it was found that the deviation shows computer models and laboratory stand less than 5%. That is to say that the research results confirm the adequacy of the computer model of the real characteristics of the electric drive. Conclusions and perspectives Analysis of studies have confirmed the adequacy of a computer model of the real characteristics of the electric deviation shows less than 5%. The results of research on computer models are suitable for use in the design phase of a thyristor controlled electric voltage regulator with pulse-phase control.